Comparative assessment of DNA extraction procedures for Ascaris spp. eggs. (2020) - Amoah, I.D.; Singh, G.; Troell, K.; Reddy, P.; Stenström, T.A.; Bux, F.
Abstract: A central and critical step in the molecular detection of soil-transmitted helminths from environmental sources is the extraction of DNA from the eggs. In this study, we investigated the yield of DNA extracted from known quantities (500, 100, 50, 20, 10 and 5) of Ascaris suum eggs, as well as directly from wastewater and sludge samples containing Ascaris spp. eggs, using six commercial DNA extraction kits. The amount of DNA extracted was quantified with NanoDrop, Qubit and Ct values from quantitative polymerase chain reaction (qPCR) assay using CFX96 Touch™ real-time PCR equipment. The PowerLyzer Ultraclean Microbial DNA isolation kit and PowerSoil DNA isolation kit gave the highest yield of DNA based on the NanoDrop, Qubit and Ct values. However, the qPCR results indicate that in some of the kits, PCR inhibitors may have been carried over to the PCR reaction. DNA extraction kits that incorporate a bead-beating step as well as other mechanical eggshell disruption steps were superior in extracting DNA from Ascaris spp. eggs. Additionally, for the accurate quantification of extracted DNA, the use of Ct values from qPCR and Qubit readings gives better results compared to the NanoDrop readings. For efficient downstream applications, the use of DNA extraction kits with superior inhibitor removal technology is essential, in addition to a high yield of DNA.